Greening in the circumpolar high-latitude may amplify warming in the growing season - Jeong, JH; Kug, JS; Kim, BM; Min, SK; Linderholm, HW; Ho, CH; Rayner, D; Chen, DL; Jun, SY (Climate Dynamics, 2012)
We present a study that suggests greening in the circumpolar high-latitude regions amplifies surface warming in the growing season (May-September) under enhanced greenhouse conditions. The investigation used a series of climate simulations with the Community Atmospheric Model version 3-which incorporates a coupled, dynamic global vegetation model-with and without vegetation feedback, under both present and doubled CO2 concentrations. Results indicate that climate warming and associated changes promote circumpolar greening with northward expansion and enhanced greenness of both the Arctic tundra and boreal forest regions. This leads to additional surface warming in the high-latitudes in the growing season, primarily through more absorption of incoming solar radiation. The resulting surface and tropospheric warming in the high-latitude and Arctic regions weakens prevailing tropospheric westerlies over 45-70N, leading to the formation of anticyclonic pressure anomalies in the Arctic regions. These pressure anomalies resemble the anomalous circulation pattern during the negative phase of winter Arctic Oscillation. It is suggested that these circulation anomalies reinforce the high-latitude and Arctic warming in the growing season. X 1 1 13 13 scie scopus